A Qualitative Study Of Emergency Nurses’ Basic Life Support Practices In A Ghanaian University Hospital (JKG (JURNAL KEPERAWATAN GLOBAL), 2021)
ABSTRACT Background: Medical emergencies are common but Sudden Cardiac Arrest (SCA) incidences are rare; yet when they occur could be life threatening leading either to disability or death. During SCA incidents, health care professionals will be required to act skilfully and swiftly to restart the heart and stabilise the patient until advanced care can be accessed or provided. There is evidence that victims of cardio and/or respiratory arrest whilst in the hospital will have improved outcomes if Cardiopulmonary Resuscitation (CPR) is initiated within three to five minutes. The objectives of this study were to find if emergency nurses were adequately resourced to practice Basic Life Support (BLS), and the ease or difficulties with which they practice BLS. Methods: This Qualitative Descriptive (QD) study was conducted at the University of Cape Coast Hospital (UCCH) between June and September 2019. Six nurses were purposively recruited for the study. All interviews were audio-recorded and transcribed verbatim. The transcription was done with Microsoft Word and transferred to Microsoft Excel for thematic analysis using an inductive descriptive approach. Data analysis took a conventional qualitative content analysis approach. Results: Four of the participants were females whilst two were males. During data aggregation and analysis, 17 first-level codes were extracted from which two themes, five categories and six subcategories were obtained for discussion. The major themes were: (1) Basic Life Support (BLS) equipment and material resources, and (2) working environment and human resource. Conclusion: The study found that nurses working at emergency ward at UCCH were adequately resourced and well prepared to practice BLS. They however had challenges as their work seem to be hindered by patients who present to the ward without emergency needs and unavailability of emergency drugs.
Keywords: basic life support; cardiopulmonary resuscitation; qualitative descriptive; emergency nurses